DESAIN ARTWORK PADA TAMAN PULAU DAN MEDIAN JALAN DI JALAN MEDAN MERDEKA JAKARTA - Sigit Mulyansyah Effendy; Dewi Rezalini Anwar (Jurnal Lanskap Indonesia, 2013)
Open space is a part of the community's needs for leisure. Open space can have many forms and functions. One of them is the traffic island and street median. Traffic Island and street median has potential as a media of display to form character and give a mental map for an area. Character of a region can be shaped with elements inside, one of these with the placement of the artwork. Artwork can be a an element mental map to guide a person to move from one point to other, especially in big cities such as Jakarta. The Medan Merdeka road is surrounded by traffic islands, up to now still not have character and appeal to form a mental map of its users. This study aims to create the artwork design can shape the character and attitudes docket in the Medan Merdeka Area. This activity is carried out on the grounds of The Medan Merdeka region in 16 weeks with the method of direct observation and interviews. The Output from this research includes the design artwork on the traffic Island to has function as a mental map in the area.